Design and kinematics analysis of a novel six-degree-of-freedom serial humanoid torso. (28th December 2017) - Li, Tao; Yao, Peng; Luo, Minzhou; Tan, Zhiying; Wang, Meiling; Guo, Ziyi
This article presents a bioinspired humanoid torso which is supposed to be used as the trunk for humanoid robots. It can effectively mimic motions of human torso with high degrees of freedom, and it has high stiffness and easy-to-control features. The main structure of the proposed torso is a six-degree-of-freedom serial mechanism with twist angles that are not equal to 0, π /2 or π and zero-length links. Forward kinematic and workspace analysis based on Denavit–Hartenberg and Monte Carlo methods have been formulated to analyze the feasibility of this structure. In addition, a hybrid method combing the large-scale regularity search capabilities of chaos optimization and the quasi-Newton method with relatively high-speed convergence has been proposed to analyze inverse kinematics. Simulations are carried out with the aim to validate the correctness and efficiency of this method for studying the inverse kinematics.